De lo bucal a lo oral, la práctica odontológica: de la técnica al sujeto - Nelson Cortes Castaño (Revista Facultad de Odontología Universidad de Antioquia, 2001)
The present study was carried out with the purpose of questioning the Dental Practice practice in which subjectivity is not present because the relationship dentist- patient is limited to the interaction of knowledge of a science with a disease of the individual that suffers it. This study is directed mainly to dentists and also to all those people that have worried about a method that has reduced the body to the dimension of an organism and have forgotten the mouth, besides being a maternal home for the organs, is also a stage that represents the subject. It questioned the speeches that have supported Natural and Social Sciences, such as medicine and psycho analysis; practices that have interpreted in a different way the relationship between the subject and his disease and that contribute with elements to understand the importance of the change of direction from the medical science to the analytic listening; the transit from the organ to the body, from the sign to the symptom, from the offer to the demand.